Pengaruh Infrastruktur Terhadap Pertumbuhan Ekonomi Di Provinsi Sumatera Barat - Muhammad Iqbal, Muhammad Iqbal; Triani, Mike (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research aims to determine the influence of infrastructure on economic growth in West Sumatra Province. This research is quantitative in type. The data used is secondary data in the districts/cities of West Sumatra Province 2015-2021 obtained from related institutions. This research uses panel data regression analysis assisted by Eviews10 software. The results of this research show that road infrastructure has a positive and significant influence on economic growth in West Sumatra Province. Electrical infrastructure has a positive and significant influence on economic growth in West Sumatra Province and agricultural infrastructure has a positive and insignificant influence on economic growth in West Sumatra Province.